TINJAUAN TINDAK PIDANA KEKERASAN PISIKIS DALAM RUMAH TANGGA - M. AKBAR SATYA F; Rika Lestari; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Addressing the family of each person will attempt to resolve it in accordance degan capabilities available to it, in which the family is the smallest social unit in society whose members are bound by a marital relationship (husband and wife) and the relationship of blood (biological children) or also stepchild or foster child (adoption). In Article 4 of Law Number 23 Year 2004 on the Elimination of Domestic Violence states that every person shall be prohibited from domestic violence teradap person within the scope of his household, by the way: Physical violence, psychological violence, sexual based violence, abandonment household. psychological violence is very difficult to prove, see kekersan psychic is an act of verbal abuse, which resulted in a decreased self-confidence, increase the fear, the loss of the ability to act and not berdaya.Kekerasan psychic can often result if the wife though increasingly dependent on her husband have made him sufferSecond, to know how to determine the occurrence of indicators of psychological violence in the household, third, to determine the steps in applying criminal offense psychic in the household.This type of research can be classified types of normative legal research, this study is descriptive, ie a study that describes in a clear and detailed review of the criminal acts of psychological violence in the home, the source of the data used secondary data consisting of primary legal materials, secondary law and tertiary legal materials, data collection techniques in this study with the literature study methods or documentary studies, after the data is collected and analyzed for the conclusions drawn.From the research and pembahansan can be concluded that, first, the cause of psychological violence in the household rumag is not just a matter of differences in gender, education level, economic, ethnic, age, and culture. But there is a more fundamental psychological violence in the household is a household member's personality be it husband, wife, son, and a maid who worked in the household environment, Second, how to determine the occurrence of indicators of psychological violence in the household that is loss of contact with reality such as schizophrenia and other psychotic or form, or which can be called depressive depressive indicators contained in the pocket book PPDGJ - III. Third, law enforcement crime of psychological violence in the home is to strengthen the law enforcement agencies in accordance with Law No. 23 of 2004Keywords: Criminal Offenses – Psychic – Domestic Violence